Oral manifestations in patients with eating disorders (Research, Society and Development, 2023)
Eating disorders (ED) correspond to a group of psychopathological disorders that affect individuals' relationship with food and their body. Bringing as a consequence harmful habits that result in emotional and functional instability and, in extreme cases, death. The dentist has an essential role in the secondary prevention of these disorders, considering that the oral cavity of these patients presents characteristic signs. However, despite the seriousness of the issue, due to the lack of training that allows reaching a diagnostic hypothesis, a significant portion of professionals are unsure about the measures to be taken. This may indirectly contribute to the worsening of the clinical condition. This work is an integrative review with the aim of evaluating the manifestations present in the oral cavity resulting from eating disorders, anorexia nervosa and bulimia nervosa, as well as bringing a perspective of the dental surgeon as a health professional about their importance in these cases.